Analisis dan Implementasi Modul Akuntasi pada Aplikasi ERP berbasis Open Source - Fadilla Arfikriyana; Suhendi Suhendi (LPPM STT Terpadu Nurul Fikri, 2022)
This study discusses implementing an accounting information system using the Odoo application at PT Delta Solusi Konsultama. PT Delta Solusi Konsultama is a consulting company that offers transfer pricing assistance/services, tax advisory, and tax compliance. In its business, PT Delta Solusi Konsultama only carries out service sales transactions but with a significant enough value. PT Delta Solusi Konsultama still records manually at the current rapid development of technology. In addition, there is a buildup of company financial records, so it takes a long time to search for data. Therefore, by applying the Accounting and Finance module to the Odoo application, it is hoped to overcome the problems at PT Delta Solusi Konsultama. The results of this study include: making a Chart Of Account (COA), recording customer data, recording service sales data, recording financial transaction journals, and printing financial reports. The Odoo application can connect users so that between divisions, there is system integration that can facilitate the control process. This research concludes that the PT Delta Solusi Konsultama Accounting Information System can run in real-time and accurately after using the Odoo application. The advice given from this research is to eliminate unused menus and apply developer mode to change user roles.